2009
DOI: 10.2215/cjn.02020408
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography and Outcome in Patients with Diabetes Mellitus on Maintenance Hemodialysis

Abstract: Background and objectives: In hemodialysis, applicable guidelines recommend regular electrocardiogram (ECG) recordings.However, respective systematic evaluations are absent. Thus, the authors investigated whether routine ECG findings add prognostic information to standard risk assessment in hemodialysis.Design, setting, participants, & measurements: The relationship between nine common baseline ECG variables and a combined cardiovascular endpoint (CVE; cardiac death, myocardial infarction, stroke), sudden deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 28 publications
0
37
2
1
Order By: Relevance
“…Furthermore, compared with our study, in the Spanish study the Cornell criteria used a different definition of EKG-LVH in that it did not include the QRS duration to calculate the voltage-duration product; thus, headto-head comparison is difficult. Krane et al reported the prevalence of EKG-LVH diagnosed by Sokolow-Lyon criteria among 1253 patients participating in the German Diabetes and Dialysis 4D study (14). All of these patients were on hemodialysis and had type 2 diabetes mellitus; therefore, the patient population was substantially different from the study presented here.…”
Section: Adjusted For Ckd+ Other+cornellmentioning
confidence: 65%
See 1 more Smart Citation
“…Furthermore, compared with our study, in the Spanish study the Cornell criteria used a different definition of EKG-LVH in that it did not include the QRS duration to calculate the voltage-duration product; thus, headto-head comparison is difficult. Krane et al reported the prevalence of EKG-LVH diagnosed by Sokolow-Lyon criteria among 1253 patients participating in the German Diabetes and Dialysis 4D study (14). All of these patients were on hemodialysis and had type 2 diabetes mellitus; therefore, the patient population was substantially different from the study presented here.…”
Section: Adjusted For Ckd+ Other+cornellmentioning
confidence: 65%
“…Krane et al reported the association of EKG-LVH diagnosed by Sokolow-Lyon criteria with cardiovascular events and mortality (14). These 1253 patients participating in the German Diabetes and Dialysis 4D study were all on hemodialysis and had type 2 diabetes mellitus; therefore, the patient population was substantially different from the study presented here.…”
Section: Prognostic Value Of Ekg-lvhmentioning
confidence: 72%
“…The HEMO Study participants were subject to exclusion criteria, such as unstable angina or New York Heart Association class IV congestive heart failure; therefore, generalization of our findings to the HD population in the United States should be done with caution. Data regarding ejection fraction, left ventricular hypertrophy, and QT interval on electrocardiography, known risk factors for SCD (particularly in the general population), were not available for all patients (36)(37)(38). In addition, cardiac biomarkers, such as troponins Hazard ratios for continuous predictors are given per 1 SD increase.…”
Section: Discussionmentioning
confidence: 99%
“…Berbagai kelainan yang dapat dideteksi dengan EKG antara lain sinus bradikardia dan takikardia, aritmia, deviasi aksis QRS, blok atrioventrikular, infark miokard, hipertrofi ventrikel kiri, blok cabang serabut kiri dan kanan (left/right bundle branch block, LBBB/ RBBB), dan interval QT terkoreksi. 27,28 Krane meneliti pada tahun 2009 mengenai berbagai gambaran EKG tersebut pada pasien PGK dan DM yang akan menjalani HD dan menilai apakah kelainan tersebut memiliki nilai prognostik terhadap kejadian kardiovaskular. Ia mendapatkan bahwa LVH dan aritmia merupakan kelainan yang berhubungan dengan peningkatan mortalitas.…”
Section: Penelitian Tahun Nilai Batas Hemoglobin (G/dl)unclassified